Avifauna of the Serra de Itabaiana National Park revisited: additions and deletions in a period of 15 years (Acta Scientiarum. Biological Sciences, 2022)
The Serra de Itabaiana National Park (PARNASI) is known as an important conservation area in the ecotone between the Atlantic Forest and Caatinga in Northeast Brazil and is one of the main areas of fauna and flora studies in Sergipe. For this reason, there are some studies on its avifauna, which date back to its creation in 2005. However, after 15 years of establishment of PARNASI, an update of the inventory of birds is necessary due to adjustments in the management of the park. The present study aimed to update the bird inventory of the Serra de Itabaiana National Park, chronologically comparing the new ornithological records obtained, aiming to contribute to the knowledge and conservation of Sergipe's avifauna. The data were compiled from scientific publications, personal files and from documented records on a specialized website. The resulting list includes 227 bird species belonging to 49 families, including Thraupidae (28 species; 12.4%), Tyrannidae (25 species; 11.1%) and Accipitridae (17 species; 7.5%) as the most representative. The most representative guilds were insectivorous (87 species; 38.3%) and omnivorous (60 species; 26.4%), and by species independent of the forest environment (87 species; 38.3%). Fourteen bird species are threatened with extinction. Nine species are endemic to the Caatinga biome, eight to the Atlantic Forest and one to the Cerrado. We added 104 species to the first checklist produced for the PARNASI created in 2005, including Nyctibius grandis (Nyctibiidae), a new record for the state of Sergipe. PARNASI's updated list of bird species allows for a better assessment of its effectiveness in the conservation of the local avifauna, facilitating management actions that allow the coexistence and perpetuation of species over time.